Segmental morphology of perennial ryegrass (Lolium perenne L.) : a study of functional implications of plant architecture : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science, Institute of Natural Resources, College of Sciences, Massey University, Palmerston North, New Zealand - Robin, Arif Hasan Khan; Robin, Arif Hasan Khan (Massey University, 2011)
This thesis investigated the structural and functional implications of segmental organisation of two hydroponically grown perennial ryegrass (Lolium perenne L.) cultivars, Alto and Aberdart in spring and autumn, for around 90 days in each season. The objectives included describing tiller axis morphology, studying leaf and root turnover pattern in a phyllochron (leaf appearance interval) time scale, and studying root-shoot and tiller-tiller functional relations. In the Spring experiment a total of 15 – 16 segments or phytomers developed, 10 – 11 of which bore roots. In the Autumn experiment, a total of 22 – 23 phytomers developed, 17 – 18 of which bore roots. New leaves appeared more frequently in autumn and achieved significantly greater final leaf length, dry weight and lamina area through a significantly faster rate of leaf extension, though with significantly shorter elongation duration compared to spring leaves. However, autumn leaves had significantly longer life span and lower specific leaf area. The individual leaves achieved maximum photosynthetic capacity between 12.5 and 14.8 days after appearance. The individual root-bearing phytomers in autumn bore a significantly higher number of roots (2.4) than in spring (1.7). At successively more developed phytomers root main axis length, root dry weight, root length including branches, surface area and volume increased linearly up to phytomer 6 – 7 for both of the cultivars in both seasons whereas dry matter deposition rate per phytomer per day and mean root diameter decreased gradually. Branching to quaternary order was observed during root development. Principal component analysis of root morphology data detected statistically significant morphological variation between genotypes of each cultivar but the basis for differentiation was not visually evident. Roots older than 10 leaf appearance intervals in autumn decreased gradually in volume while still increasing in total branch length. This was interpreted as evidence of root death in some branches while the remainder continued elongation. Tiller root:shoot ratio varied seasonally, possibly mediated by faster leaf than root appearance rate at successive phytomers in spring, and vice-versa in autumn. Excision of adult daughter tillers significantly reduced number of root-bearing phytomers of the main tiller which indicated slower new root appearance rate at the main tiller. A significant proportion of root derived N and assimilated C from daughter tillers was translocated to the main tillers and this may explain why daughter tillers remain smaller in size than their parent tillers. Evidence for a proposed oscillation of N concentration within the tiller axis of Hordeum vulgare L. linked to N uptake by successive developing leaves was also examined. A weak N concentration oscillation was detected, with the highest concentration just prior to each leaf appearance event. Evaluation of ryegrass root morphology from a segmental perspective, though logistically challenging, has provided previously unavailable information on the time course of root mass accumulation and of root branching. This methodology could be used in future to further explore the carbon economy of the root system and the factors that limit final root size.
Keywords: Ryegrass cultivars; Ryegrass physiology; Ryegrass roots